ENCOURAGING STUDENTS TO SPEAK THROUGH INSIDE-OUTSIDE CIRCLE TECHNIQUE - Sulung, Susi; Sutapa Y., Y. Gatot; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of this research was to find out how the Inside-Outside Circle technique encourage the students to speak English. The participants of this research were 32 students who joined Science Program 1 (A1) of the eleventh grade.This classroom action research was conducted in 3 cycles. In cycle 1, the data revealed that the students had poor encouragement in speaking, felt anxious, lack of vocabulary mastery and have low ability in pronunciation. In cycle 2, the teacher implemented additional techniques; brainstroming and drill. The data revealed good improvement, however the students still have low ability in pronunciation and vocabulary mastery. In cycle 3, the teacher implemented additional techniques; brainstroming, drilling, and reading aloud. The data showed that the students were active than two previous cycles, the students have better improvement in pronunciation and vocabulary mastery. In brief, this present findings proved that Inside-outside circle technique can be the alternative way to encourage the students to speak and also helped solve their problem in speaking. Â Keywords: Inside-outside circle technique, encourage students to speak Â Abstrak: Penelitian ini bertujuan untuk menyelidiki bagaimana teknik Inside-Outside Circle mendorong siswa berbicara bahasa Inggris. Participan dari penelitian ini terdiri dari 32 orang siswa yang tergabung di kelas XI program Ilmu Alam 1 (A1). Penelitian tindakan kelas ini dilakukan sebanyak 3 cycle. Di cycle 1, data menunjukkan bahwa siswa memiliki dorongan yang rendah dalam berbicara, merasa takut, kekurangan kosakata dan memiliki kemampuan yang rendah dalam pengucapan. Di cycle 2, guru menerapkan teknik tambahan; brainstroming dan drill. Data menunjukkan peningkatan yang baik, akan tetapi siswa tetap memiliki kemampuan yang rendah dalam pengucapan dan penguasaan kosakata. Di cycle 3, guru menerapkan teknik tambahan; brainstroming, drilling, dan reading aloud. Data menunjukkan siswa lebih aktif daripada dua cycle sebelumnya, siswa juga memiliki peningkatan yang lebih baik pada kemampuan pengucapan dan penguasaan kosakata. Secara singkat, hasil penelitian ini menunjukkan bahwa teknik inside-outside circle bisa menjadi salah satu cara untuk mendorong siswa berbicara dan juga membantu siswa memecahkan masalah dalam berbicara. Â Kata kunci: teknik Inside-outside circle, mendorong siswa berbicara